Implicações das prescrições de nível operacional sobre a estabilidade e flexibilidade de organizações de alta confiabilidade - Rodrigues, Francisco Schuster (2019)
Prevailing organizational literature recognizes two opposite and contradictory types of organizational structure: bureaucratic and organic. The former is appropriate in more stable environments where control and autonomy are centralized to provide stability. The latter fits more adequately in dynamic environments where decentralization and flexibility are strongly necessary. Despite this contradiction, high reliability organizations do not operate in accordance with prevailing organizational literature. An important feature of high reliability organizations is its capability to change between stable and flexible modes of performance under uncertainty. High reliability organizations are intractable systems characterized by unpredictability, fast pace of change and limited comprehensibility, which require flexibility. But at the same time, exhibit high impact to society that, in response, impose bureaucratic mechanisms of systems control, such as strong formalization of work demonstrated by high dependence of prescriptions. Grounded in recent studies of organizational science domain along with well-established safety management literature related with work formalizations, this study aims to discuss the implications of prescriptions over stability and flexibility in high reliability organizations. Findings from a multiple case study in oil and gas industry with drilling and production companies are presented. Results suggest that different prescriptions offer different degrees of control and autonomy, depending on the type of prescriptions and its latitude of applicability. Thus, properly designed work formalizations can enable not only stable mode of performance, but also flexible mode to foster high reliability. The literature usually views prescriptions as a centralizing mechanism of control which promote stability. However, from a theoretical point of view, this study supports a duality view, where prescriptions provide decentralized control and consequently promote flexible mode of performance either.